Elevating surgical outcomes: a comprehensive analysis of innovative nursing practices in intraoperative care across diverse specialties - Guo, Ling; Zuo, Huanying; Sun, Yongmei; Qian, Chengcheng (Frontiers in Medicine, 2025)
The landscape of surgical care is undergoing a profound transformation, driven by rapid advancements in technology and a persistent focus on enhancing patient outcomes. At the forefront of this evolution are innovative nursing practices within the intraoperative setting, which are proving instrumental in elevating patient safety, optimizing operational efficiency, and significantly reducing complications across a spectrum of surgical specialties. This report provides a comprehensive analysis of these cutting-edge nursing interventions from the foundational principles of perioperative care to the integration of advanced technologies such as Artificial Intelligence (AI), robotics, virtual reality, and personalized medicine. Perioperative nurses, traditionally recognized for their critical roles in maintaining sterile environments and advocating for patient wellbeing, are now embracing expanded responsibilities as technological integrators, data interpreters, and champions of evidence-based protocols such as Enhanced Recovery After Surgery (ERAS). The adoption of these innovative practices has led to demonstrable improvements, including shorter hospital stays, reduced opioid consumption, and decreased complication rates. However, the path to widespread adoption is not without its challenges, encompassing human factors such as resistance to change, organizational barriers such as insufficient resources, and technical complexities related to data accuracy and regulation. To fully harness the potential of innovative intraoperative nursing, healthcare organizations must strategically invest in continuous, accessible training programs that balance technological proficiency with core nursing judgment. Cultivating a culture that empowers nurse-led innovation, prioritizes human-centered technology design, and strengthens multidisciplinary collaboration is paramount. Furthermore, a commitment to evidence-based implementation and addressing health equity in technology access will ensure that advancements benefit all patients and that the nursing profession continues to thrive as a vital force in shaping the future of surgical care.